Forecasting Traffic and Toll Revenue for Kathmandu-Terai/Madhesh Fast Track Expressway - Lamsal, Sandesh; Khatiwada, Purushartha; Pradananga, Rojee; Shrestha, Pradeep Kumar; Marsani, Anil (KTFT Journal, 2024)
Analysis of traffic forecasting and toll revenue projections for the Kathmandu-Terai/Madhesh Fast Track (KTFT) Expressway, which is Nepal’s first Expressway connecting Kathmandu to Nijgadh. The analysis involves an Origin-Destination survey, traffic assignments and projections, and an evaluation of toll earnings. Traffic assignment of the existing traffic between Kathmandu various regional zones in Nepal shows an estimated 40% diversion of traffic to the KTFT Expressway. Utilising daily volume records of Department of Roads (DoR) for Nagdhunga and Banepa Bardibas highway sections, a projected daily traffic volume of 11957 passenger car unit (PCU) was determined for the base year 2024. Traffic forecasts for 2035, 2045 and 2055 were made by projecting the base year traffic and considering a generated traffic of 30% of the diverted traffic for each subsequent year. Growth rates for different vehicle types were projected using elasticity method with GDP as an indicator. The total daily traffic projected for 2035, 2045 and 2055 is 30922 PCU, 48789 PCU and 70724 PCU, respectively representing approximately 2.59, 4.08, 5.91 times the base year volume. A toll pricing structure, in accordance with the guidelines in the National Highway Fee Rules (NHFR-2008) has been proposed. Under this toll structure, projected daily total revenue for years 2035, 2045, and 2055 are estimated to be NRs 60.53 lakhs, NRs 160.62 lakhs, and NRS 251.40 lakhs, respectively. Comparison of this revenue with the construction and maintenance costs of the project indicates an estimated payback period of 35 years to break even on the construction cost.